Cardiac STAT3 Deficiency Impairs Contractility and Metabolic Homeostasis in Hypertension - Altara, Raffaele; Harmancey, Romain; Didion, Sean P.; Booz, George W.; Zouein, Fouad A. (Frontiers in Pharmacology, 2016)
Signal transducer and activator of transcription 3 (STAT3) protects the heart from acute ischemic stress. However, the importance of STAT3 to the heart in chronic stress, such as hypertension, is not known. To study this, we used cardiomyocyte-targeted STAT3 knockout (KO) mice and Angiotensin II (ANG II) infusion by osmotic minipumps. After 4 weeks, ANG II induced similar cardiac hypertrophy in wild type (WT) and cardiac Cre-expressing control (CTRL) mice with no impairment of cardiac function. In contrast, STAT3 KO mice exhibited reduced contractile function but similar hypertrophy to CTRL mice. Ejection fraction and fractional shortening decreased by 22.5 and 27.3%, respectively. Since STAT3 has direct protective effects on mitochondrial function, we examined rates of glucose and oleate oxidation by isolated perfused hearts using a Langendorff system. Hearts of ANG II-treated STAT3 KO and CTRL mice had similar rates of oleate oxidation as saline-infused WT mice. Rates of glucose oxidation were similar between hearts of WT plus saline and CTRL plus ANG II mice; however, glucose oxidation was increased by 66% in hearts of ANG II-treated STAT3 KO mice. The ratio of maximal ATP yield from glucose to fatty acid oxidation was 21.1 ± 3.1 in hearts of ANG II-treated STAT3 KO mice vs. 12.6 ± 2.2 in hearts of ANG II-treated CTRL mice. Lactate production was also elevated in hearts of ANG II-treated STAT3 KO mice by 162% compared to ANG II-treated CTRL mice. Our findings indicate that STAT3 is important for maintaining contractile function and metabolic homeostasis in the hypertensive heart, and STAT3 deficiency promotes a switch toward glucose utilization.